"The truth of what's happening" How Tibetan exile media develop and maintain journalistic authority. (February 2023) - Crete-Nishihata, Masashi; Tsui, Lokman
Tibet is one of the most restrictive places in the world for press freedom, with information online and offline tightly controlled and censored by the Chinese government. Foreign correspondents are restricted from travelling to and reporting in Tibetan areas, while Tibetans who act as sources are often persecuted. Despite this level of repression, Tibetans still find ways to tell the rest of the world what is happening in Tibet. This paper explores how it is possible to authoritatively report on events in one of the world's most restrictive places for press freedom. Instead of relying on a single individual or news organisation, we find that reporting is conducted through journalistic networks consisting of sources in Tibet, Tibetan exile journalists, and source intermediaries called 'communicators'. Based on fieldwork and semi-structured interviews with Tibetan journalists and communicators we explore how they develop and maintain journalistic authority, while being in exile and having to deal with severe constraints to press freedom.